Iowa RBA, August 27, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for August 27, 1996. Highlights of the update include sightings of a Rufous Hummingbird, Red Crossbills, Red Knots, Snowy Egrets, and Little Blue Herons. Also included are handwritten notes for the next week's update with sightings of Red Phalaropes and 16 species of shorebirds, including Buff-Breasted Sandpipers and Black-bellied Plovers. Epson - sheet feed/flatbed